1988
DOI: 10.1017/s0021859600082198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green manuring and mineral fertilizer on growth and yield of crops in rice-based cropping on acid lateritic soil

Abstract: SummaryGreen manuring in situ with sunnhemp (Crotalaria juncea) and dhaincha (Sesbania aculeata) significantly improved growth and yield of transplanted rice. Giving the green manure crops 15 kg N/ha or 15 kg N and 30 kg P2O5/ha further increased yield. Interaction between green manuring and N fertilizer revealed that a considerable quantity of fertilizer N (45–60 kg N/ha) applied to rice could be replaced by incorporation of green manure crops to which a small amount of fertilizer had been applied. Residual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Yet even after Sesbania, additional fertilizer N was required to realize the full potential productivity of maize. The saving of N through incorporation of residues of grain legumes such as cowpea and greengram was reported to vary from 30-60 kg Nha −1 (Ali 1992;Phoomthaisong et al 2004;Baijukya et al 2005) and 60-120 kg Nha −1 through green manure of Sesbania in cereal crops like rice and maize (Sharma and Mittra 1988;Kaytal 1993;Mahapatra and Sharma 1995;Sharma et al 1998;Sharma and Prasad 1999;Sharma 2005). Besides the direct addition of N through the above-ground biomass, the legumes may enhance the soil available N pool for following crops via root exudates or inefficiencies in recovering soil mineral N during the legume phase, and subsequent decomposition of root and nodule residues (Ghosh and Singh 1994;Chalk 1998;Herridge et al 1995;Ghosh et al 2007).…”
Section: Nitrogen Economy Through Legumesmentioning
confidence: 99%
“…Yet even after Sesbania, additional fertilizer N was required to realize the full potential productivity of maize. The saving of N through incorporation of residues of grain legumes such as cowpea and greengram was reported to vary from 30-60 kg Nha −1 (Ali 1992;Phoomthaisong et al 2004;Baijukya et al 2005) and 60-120 kg Nha −1 through green manure of Sesbania in cereal crops like rice and maize (Sharma and Mittra 1988;Kaytal 1993;Mahapatra and Sharma 1995;Sharma et al 1998;Sharma and Prasad 1999;Sharma 2005). Besides the direct addition of N through the above-ground biomass, the legumes may enhance the soil available N pool for following crops via root exudates or inefficiencies in recovering soil mineral N during the legume phase, and subsequent decomposition of root and nodule residues (Ghosh and Singh 1994;Chalk 1998;Herridge et al 1995;Ghosh et al 2007).…”
Section: Nitrogen Economy Through Legumesmentioning
confidence: 99%
“…Higher uptake of 4 to 8 kg N/ha under the green manure treated plots than that from unfertilized control explained the residual effect of the green manures on chickpea. SHARMA and MiTTRA (1988) and LADHA et al (1989) also reported the residual effect of green manures applied to preceding rice on grain yields of succeeding chickpea and wheat crops.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of chemical fertilizer does not diminish the utility of organic sources (CHANG 1975), which are known to maintain soil ferrili-t}' for better rice production (SHARMA and MiTTRA 1991). The high cost of fertilizers and the low purchasing power of peasants also restrict the use of costly fertilizer inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Green manure approaches to crop production may improve economic viability whilst at the same time reducing the environmental impacts of agriculture. Indeed, unlike synthetic N fertilizers, legumes utilized as GM represent a potentially renewable source of on-field, biologically fixed N and may also fix and add large amounts of C to cropping systems (Hargrove 1986;Sharma and Mittra 1988). Among the most widely used temperate legumes often included are those in the genera Trifolium (clovers), Vicia (vetches), Medicago (alfalfa and other medics) and Lupinus (lupins).…”
Section: Discussionmentioning
confidence: 99%